Mechanically ductile, ionically conductive and low-temperature tolerant hydrogel enabled by high-concentration saline towards flexible strain sensor. (1st December 2022) - Li, Shi-Neng; He, Xiao-Feng; Zeng, Zi-Fan; Jiang, Baiyu; Wu, Qiang; Gong, Li-Xiu; Li, Yang; Bae, Joonho; Wang, Siqun; Tang, Long-Cheng
Abstract: Achieving a good trade-off between high mechanical performance and long-term strain sensing of hydrogel materials in cold environmental conditions remains a great challenge in the engineering fields, such as wearable electronics and human-machine interfaces. Herein, we propose a mechanically ductile, ionically conductive, anti-freezing ionic-type nanocomposite hydrogel for strain sensing under low-temperature environments. Typically, the combination use of chain-entanglement structure induced by saturated sodium chloride and nano-reinforcement produces the resultant hydrogel with the advantages of highly enhanced and balanced mechanical properties, reliable freezing-tolerance (−56.8 °C) and improved electric performance. Notably, the strain sensor based on such ionic-type nanocomposite hydrogels exhibits intriguing sensing performance, including high sensitivity (gauge factor: 6.67), fast response (≈120 ms) as well as wide detection range (0–1216%). Owing to exceptional low-temperature tolerance of the hydrogels, the optimized sensor reveals a highly enhanced low-temperature adaptability and splendid sensing performance with good capacity retention (97.6% and 90.5% for electrical conductivity and gauge factor, respectively) even after storing for 30 days at − 20 °C. Furthermore, the strain sensor can accurately detect and distinguish both large mechanical deformation and human motions under harsh environment, reflected by the unique characteristic signal with stable repeatability (e.g., a strain of 200% with 200 cycles). Clearly, the versatile multi-functionalities of high-concentration ionic nanocomposite hydrogels prepared herein could provide a new perspective for the design and fabrication of advanced all-round ionic sensor for promising applications in extremely harsh low-temperature environments. Graphical Abstract: ga1 Highlights: The hydrogel exhibits prominent features composed of mechanical robustness, freezing resistance and ionic conductivity. The combination of high-concentration NaCl and nano-reinforcement contributes to splendid integrated properties. The composite hydrogel displays sensitive strain-induced resistance change under various deformations. A hydrogel sensor can accurately monitor multi-scale deformation in ambient and cryogenic environment.